Mulheres intérpretes do Maranhão: perfis e concepções de cultura - MACHADO, Andressa de Carvalho (2018)
The present dissertation analyzes the profiles and positions of eight women who constitute themselves as spokesmen of the "Maranhão culture" in different segments of action: literature, crafts, plastic arts, heritage, cuisine, performing arts, music and popular culture. The investigation is part of a research agenda developed within LEEPOC on the trajectories of Maranhão interpreters, conceptions of "culture", "politics" and "society" and constructions of regional identity. Approaching the interconnections of the political and cultural domains from the profiles and modes of action of agents, who occupy relatively privileged positions in the cultural space of Maranhão, we show how the interconnections of affective, professional, political and technical dimensions, among others, are reflected in conquest of authorized positions as formulators of cultural goods and representation on the social world. As well as in the reproduction of positions of submission to a traditional order, thus defining the gender relations in these domains.